Soil Moisture Affects the Rapid Response of Microbes to Labile Organic C Addition - Bian, Hongfeng; Li, Chao; Zhu, Jianxing; Xu, Li; Li, Mingxu; Zheng, Shuai; He, Nianpeng (Frontiers in Ecology and Evolution, 2022)
Pulsed inputs of labile organic carbon (LOC) are common in soils and significantly affect carbon cycling. However, it remains unclear how soil moisture content affects microbial responses to LOC inputs and the relative contributions of native soil organic matter (SOM) and LOC derived from CO2 emissions during this process. In this study, we aimed to elucidate how moisture content affects microbial response to LOC inputs and native SOM. Here, 13C-labeled glucose was added to soils under nine soil moisture treatments (ranging from 10%–90% of the water holding capacity (WHC)), and the immediate utilization of LOC and native SOM by microbes was measured We found that the response of soil microbes to LOC was rapid, and promoted native SOM decomposition. Soil moisture content influenced the microbial usage of LOC and native SOM. A soil water content of 60% WHC was the optimal threshold for changes in the proportion of LOC and native SOM utilized by the microbes. Specifically, we found that when the soil moisture content was below 60% WHC, the ratio between LOC and native SOM increased with increasing moisture content levels. It gradually decreased when the soil moisture content was above 60% WHC. Overall, these findings emphasize the important role of moisture and LOC inputs in soil C cycles.